Pengaruh Pendidikan Kewarganegaraan terhadap Sikap Nasionalisme Siswa dan Peran Pendidikan Kewarganegaraan dalam Menumbuhkan Sikap Toleransi - Ahmad Syihabuddin Hasibuan; Syamzaimar Syamzaimar (International Forum of Researchers and Lecturers, 2026)
Civic Education (CE) plays a crucial role in shaping national character amidst the challenges of disintegration in the era of globalization. This study aims to analyze the extent of Civic Education's influence on strengthening students' sense of nationalism and the strategic role of this subject in fostering a sense of tolerance within the diverse Indonesian society. The method used in this study is a literature review with a qualitative descriptive approach. The research findings indicate that an effectively implemented Civic Education curriculum can significantly enhance patriotism, awareness of rights and obligations, and pride in national identity among students. Furthermore, CE functions as an instrument of value education that teaches democratic principles and respect for differences in ethnicity, religion, race, and inter-group relations. Through an understanding of national insight and national integration, students are encouraged to develop inclusive and moderate attitudes. The conclusion of this study emphasizes that the success of Civic Education is measured not only by cognitive mastery but by the transformation of student behavior that reflects a high spirit of nationalism and the practice of tolerance in daily life, thereby creating social harmony within the framework of the Unitary State of the Republic of Indonesia.